Management of an Endobronchial Pulmonary Paraganglioma via Bronchoscopic Resection - Khuyen Hoang; Michael V. Brown; Arash Badiei; Phan Nguyen (Respirology Case Reports)
ABSTRACT Paragangliomas are rare neuroendocrine tumours sharing embryological origins with phaeochromocytomas but differ in that they are found outside the adrenal medulla. The prevalence in literature ranges from 2 to 8 cases per million people. Pulmonary paragangliomas account for approximately 2% of this. Paragangliomas can cause symptoms due to the secretion of catecholamines. Other ‘non‐functional’ paragangliomas may cause symptoms relating to mass effect or endobronchial obstruction. Once a diagnosis is made, the most common reported modality of management are lobectomy and endobronchial sleeve resection. Only a limited number of case reports describe other management modalities such as endobronchial ablation. We present the case of 48‐year‐old female with a right main bronchus endobronchial lesion identified on positron emission tomography (PET) dotatate scan on a background of succinic dehydrogenase B gene mutation (SDHB) familial paraganglioma. Bronchoscopic management with argon plasma coagulation (APC) probe ablation was used to debulk the lesion which resulted in excellent symptomatic improvement and stability on follow‐up.